Pengembangan media pembelajaran video interaktif pada materi pengeritingan desain - hasanah, luluk iliatul (Jurnal Tata Rias, 2021)
Abstract This study is R&D of interactive video on hair curling lesson and this is the other form of learning media that complete the common one. This video shows the lesson with video, animation, audio, and the question for final evaluation. The result that can be reached from this learning media making is knowing the appropriateness of the interactive video media on hair curling design lesson by the experts. Also to make it easy for teacher to deliver the lesson by online or in a classroom. The result of the appropriateness of this interactive video media on hair curling design lesson by experts is : the presentation of the score is 86,25% with a little repair, the experts said that the interactive video media on hair curling lesson is appropriate to try during the lesson section. Keywords: Lesson, Interactive Video, Hair Curling Design